Gammera, the invincible - Yuasa, Noriaki, 1933-2004; Takahashi, Niisan, 1926-2015; Dekker, Albert, 1905-1968; Harris Associates, Inc.; Cinetel Films ([Los Angeles, CA] : Harris Associates, 1966)
An atomic explosion awakens Gammera--a giant, fire-breathing turtle monster--from his millions of years of hibernation. Enraged at being roused from such a sound sleep, he takes it out on Tokyo. --
This is the American version of a Japanese motion picture. The original film was released as, Giant monster Gamera in 1965. This American version inserts new scenes and is in English. Released in association with Daiei Motion Picture Co. Ltd.
Albert Dekker, Brian Donlevy, Diane Findlay, John Baragrey, Dick O'Neill, Eiji Funakoshi, Michiko Sugata, Harumi Kiritachi.
Cinematographer, Julian Townsend, Nobuo Munekawa; editor, Ross-Gaffney; music, Wes Farrell.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: Monsters -- Drama; Science fiction films; Monster films; Feature films; Internet videos; Streaming video